Analisis Kelayakan Fasilitas Bengkel Teknik Kendaraan Ringan di SMK Negeri 1 Nisam - Rahmad Maulana; Ferry Safriwardi; Jumadi Jumadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to see how the condition and completeness of the facilities and infrastructure of the light vehicle engineering workshop at SMK Negeri 1 Nisam. The research method was carried out by conducting interviews with the relevant teachers in the workshop, and observation of data on school documents related to light vehicle engineering workshop facilities. The results showed that the results achieved were 55%, so it can be interpreted that the achievement criteria are included in the feasible category. So the conclusion that can be obtained is that it proves that there is still a level of awareness of practicum equipment users to carry out maintenance on the tools used for practicum activities.